Phytochemistry of plants from genus rauvolfia - Kumar, Brijesh; Kumar, Sunil; Bajpai, Vikas; Madhusudanan, K. P. (Boca Raton : CRC Press, 2020)
Rauvolfia species, commonly known as Sarpagandha, has been traditionally used in Ayurveda for curing high blood pressure, hypertension, snake bites, fever, and mental illnesses. Due to its wide variety and differences in chemical composition, it is necessary to develop an efficient and reliable method for rapid screening and determination of phytochemicals in the extracts of the Rauvolfia species. This book will provide qualitative and quantitative comparative phytochemical investigations of selected medicinal plants from the Rauvolfia genus using liquid chromatography-mass spectrometry (LC-MS) techniques. The results will help in assuring the efficacy and safety of Rauvolfia herbal products. Features: Collection of Ayurvedic features and scientific evidence of important medicinal plants. Discusses chemical signatures for the identification of Rauvolfia (Sarpagandha) and its products. Easy-to-use analytical procedure for quality control of Rauvolfia and its products.
OCLC-licensed vendor bibliographic record.
Keywords: Rauvolfia; Rauvolfia -- Therapeutic use; Botanical chemistry; MEDICAL / Pharmacology; SCIENCE / Chemistry / General